Antusiasme Belajar Siswa terhadap Pembelajaran Digital Berbasis BCS-App pada Masa Pandemi COVID-19 - Dian Khoirul Huda (Jurnal Didaktika Pendidikan Dasar, 2021)
The 21st century requires human to be able to take advantage of technology, including in education. The COVID-19 pandemic is also pushing education to change from classic learning to distance learning utilizing digital technology. This matter encourages teachers to carry out a learning innovation by creating learning media that is able to encourage students to be more enthusiasm about long distance learning. The digital learning media of innovation in this research can be increase student’s enthusiasm for learning in class 8.1 of Sekolah Menengah Pertama Negeri 2 Praya Barat Daya. The method used in this research is Research and Development (R&D) with testing using media validation instrument, enthusiasm observation instrument and test questions instrument given to students. Obtained in average value of the media validation results of 88.33 with very good criteria, thus it can be said that the digital learning media of innovation in this research is suitable for use in learning. The results of the observation showed that the student’s enthusiasm for learning had increased, in first learning obtained an average score of 54.12 increased at the second learning to 84.70%. Learning outcomes also increased, in first learning the average score of students was 67.06 with classical completeness of 52.94% increased in second learning the average score of students became 83.76 with classical completeness of 88.24%.